Exergy analysis for docosahexaenoic acid production by fermentation and strain improvement by adaptive laboratory evolution for Schizochytrium sp. (February 2020) - Ren, Lujing; Sun, Xiaoman; Zhang, Lihui; Huang, He; Zhao, Quanyu
Graphical abstract: Highlights: Exergy analysis was performed for DHA fermentation and ALE of Schizochytrium sp. The total exergy efficiency was 64.66% under 4 g L −1 KH2 PO4 conditions. The exergy efficiency of DHA was not more than 20.9% based on experimental data. There was positive correlation between biomass yield and exergy efficiency of DHA. Rapid growth of the evolved strain improved exergy efficiency of DHA after ALE. Abstract: Exergy analysis is powerful tool for process optimization and mechanism analysis. In this study, exergy analysis was performed for docosahexaenoic acid (DHA) fermentation process. More than 86% of input exergy was contributed by glucose. The exergy of biomass was about 64.66% of the total output exergy when the phosphate concentration was 4 g L −1 . The exergy efficiencies of DHA (ηDHA ) for the starting strains and the evolved strains under high oxygen concentration, low temperature, and two-factor conditions were also investigated. The ηDHA in the collected experimental data was not more than 20.9%. It was proved that there was a positive correlation between ηDHA and the biomass yield. It was indicated that adaptive laboratory evolution (ALE) improved biomass yield which had the most important effect on enhancing ηDHA and DHA yield (or DHA productivity). It is necessary to improve ηDHA through process optimization and ALE in future.